THE BENEFITS OF NANOSTRUCTURED TRANSDERMAL HORMONAL REPLACEMENT THERAPY IN OROFACIAL HARMOZIZATION TREATMENT: CASE REPORT - Maso, Adelaide; Tramontini, Luciene (Health and Society, 2023)
The demand for aesthetic and rejuvenating treatments is increasing in society, with that the demand for orofacial harmonization increases exponentially every day. Orofacial harmonization is a set of procedures performed by the Dentist / Dental Surgeon, which aims at the aesthetic and functional balance of the face. Steroid hormones are of great importance in aging due to the decrease of some during this process. However, poor diet including sugar consumption, changes in the sleep cycle, alcohol use, tobacco, lack of exercise and excessive exposure to UV rays also contribute to aging. We present the case of a female patient, 47 years old, who had failures in her menstrual cycle for more than 6 months, and the presence of melasma. Laboratory tests revealed changes in her hormone and vitamin levels, the clinical examination reported dry skin with blemishes, and she also reported excessive fatigue. In order to stabilize melasma and improve the appearance of the skin and obtain a better result in orofacial harmonization, bioidentical steroid hormone replacement therapy and vitamin supplementation were performed. Within 3 months of starting therapy with testosterone, progesterone, melatonin, vitamin D, and supplementation with nutraceuticals, it was observed that during treatment the patient showed a change in the appearance of her skin. The results show that in order to obtain a good response to the orofacilli harmonization treatment, it is extremely important to have a correct homeostasis.